Acts : an exegetical commentary - Keener, Craig S., 1960- (Grand Rapids, MI : Baker Academic, 2012)
"Highly respected New Testament scholar Craig Keener is known for his meticulous and comprehensive research. This commentary on Acts, his magnum opus, may be the largest and most thoroughly documented Acts commentary available. Useful not only for the study of Acts but also early Christianity, this work sets Acts in its first-century context. In this volume, the first of four, Keener introduces the book of Acts, particularly historical questions related to it, and provides detailed exegesis of its opening chapters. He utilizes an unparalleled range of ancient sources and offers a wealth of fresh insights. This magisterial commentary will be a valuable resource for New Testament professors and students, pastors, Acts scholars, and libraries"--Publisher description.
Vol. 1. Introduction and 1:1-2:47 -- Vol. 2. 3:1-14:28 -- Vol. 3. 15:1-23: 35 -- Vol. 4. 24:1-28:31.
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries